Superconducting control for surge currents. - Paul, W. (IEEE spectrum)
Systems designed to use superconductors to limit fault currents in power grids are undergoing testing. The authors describe superconducting fault current limiters (SCFCL) which may be categorised into resistive or shielded core types. The features and operation of each type of device are outlined. Both the shielded-core and resistive types of SCFCL use the same amount of superconductor material to achieve a given limitation behavior. This is because the rated power per volume of conductor is determined by the product of fault-induced field and critical current, which is the same for both devices, assuming the same type of superconducting material is employed. The shielded-core limiter works only with AC currents and is much larger and heavier than the resistive SCFCL. While there is only one large program left in the low-temperature type of SCFCL, more than 10 major projects are under way worldwide on the high-temperature type of device. The main reason is the lower HTS cooling cost